Korelasi Karakteristik Pasien dengan Biaya Perawatan Pasien Stroke Iskemik Geriatri - Nugraha, Dhanang Prawira; Aditya, Martanty (Fakultas Kedokteran Universitas Trisakti, 2024)
Background Ischemic stroke is a degenerative condition that primarily affects the elderly and has high treatment expenses. There is no data on how much it costs to treat stroke patients in Indonesia, and there are many factors that influence the cost of ischemic stroke treatment, particularly in geriatric patients. Methods This study was conducted from October to December 2018 using a cross-sectional technique. In this study, 53 patients who met the exclusion and inclusion criteria were employed as samples. The patient's characteristics, such as age, gender, length of stay, number of comorbidities, and drug quantities, are the independent variables in this study. The cost of treatment is the dependent variable. Data was acquired utilizing data collecting sheets from hospital information systems and medical records. The Spearman test and the eta test were conducted with 95 percent confidence to determine the correlation between patient characteristics and treatment costs, and the value of R was used to determine the strength of the correlation between variables. Results According to the findings, the average cost of treatment for geriatric ischemic stroke patients was Rp 5,144,083 Rp 4,423,794. The length of stay (p-value 0.05; R=0.756), the number of comorbidities (p-value 0.05; R=0.44), and the number of drugs (p-value 0.05; R=0.60) all had a significant correlation with the cost of treatment. Conclusions The factors that significantly affect the cost of hospitalisation for geriatric ischemic stroke patients are the length of stay, number of comorbidities, and number of drugs.